Book Review: The Cambridge Companion to Biblical Wisdom Literature (Part 1) - Mapule, Ashar; Ardin Sitompul (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
The book titled The Cambridge Companion to Biblical Wisdom Literature, written by Katharine J. Dell, Suzanna R. Millar, and Arthur Jan Keefer, and published by Cambridge University Press, aims to provide valuable information about the writing of Old Testament books with the hope of assisting anyone studying these books. This book focuses on texts that fall within the genre of literature and poetry, specifically the books of Job, Proverbs, and Ecclesiastes. It presents the historical and cultural background of ancient Egypt and the Near East during that time and its relation to the writing of literary and poetic books such as Job, Proverbs, and Ecclesiastes, as well as the theological values contained within them. Overall, this book is highly recommended for theological studies related to books within the genre of literature and poetry.